2013
DOI: 10.1016/j.exphem.2013.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping roles for endothelial selectins in murine hematopoietic stem/progenitor cell homing to bone marrow

Abstract: Selectins are carbohydrate-binding adhesion molecules critically involved in leukocyte recognition of endothelium. The endothelial selectins have been implicated in homing of hematopoietic stem/progenitor cell(s) (HSPC) to the bone marrow (BM) during bone marrow transplant (BMT), but the precise role(s) of individual selectins in this process have never been defined. BMT of lethally irradiated mice lacking both endothelial selectins (E/P KO) with limiting numbers of wild-type BM cells rescued significantly few… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Previous studies had shown CD44 is highly expressed on adult HSC 57 and early erythroid progenitors, but down-regulated during lineage commitment. 24 In addition, adult BM cells with colony-forming-unit granulocytes-macrophage and burst-forming unit-erythroid are H. Cao et al 32 haematologica | 2016; 101(1) Figure 6.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies had shown CD44 is highly expressed on adult HSC 57 and early erythroid progenitors, but down-regulated during lineage commitment. 24 In addition, adult BM cells with colony-forming-unit granulocytes-macrophage and burst-forming unit-erythroid are H. Cao et al 32 haematologica | 2016; 101(1) Figure 6.…”
Section: Discussionmentioning
confidence: 96%
“…24,25 BM transplantation studies into lethally irradiated mice lacking both endothelial selectins revealed that these mice exhibited a substantial defect in HSPC homing and a reduced survival that was rescued following the expression of either E-or P-selectin. 26 These and several other independent lines of evidence have highlighted vascular-selectindependent interactions as central to the recruitment of HSPC to BM. [26][27][28][29] In the current study, we determine the link between CD34 expression and the concurrent hematopoietic activation that leads to its improved homing and whether these vascular selectins can explain the gap in our understanding of this process.…”
Section: Introductionmentioning
confidence: 86%
“…26 These and several other independent lines of evidence have highlighted vascular-selectindependent interactions as central to the recruitment of HSPC to BM. [26][27][28][29] In the current study, we determine the link between CD34 expression and the concurrent hematopoietic activation that leads to its improved homing and whether these vascular selectins can explain the gap in our understanding of this process. We revealed a more defined role for CD34 as a vascular selectin ligand and showed that it has comparable affinity and functional performance to other selectin ligands on human HSPCs.…”
Section: Introductionmentioning
confidence: 86%
“…hematopoietic cells [24]. The CD34 sialomucin receptor is one of the several adhesions involved in the intra and extramedullary homing of progenitor cells into distinct microenvironments [25,26].…”
Section: Cd34 + Hematopoietic Stem and Progenitor Cellsmentioning
confidence: 99%